Phthalides as promising insecticides against Tuta absoluta (Lepidoptera: Gelechiidae) - Farias, Elizeu de Sá (2017)
The tomato leafminer Tuta absoluta (Meyrick) is an important pest of Solanaceae crops. This pest is mainly controlled with insecticides. However, few active ingredients are currently efficient against T. absoluta due to the high level of resistance of populations of this pest to the recommended insecticides. Thus, the demand for new molecules with potential use in the control of the tomato leafminer is constant. In this work, we evaluated the insecticide potential of eight phthalides derived from furan-2(5H)-one against T. absoluta larvae. We determined the potency of the most active phthalides and the susceptibility of six different T. absoluta populations to these compounds. We also evaluated their toxicity to two non-target species (Solenopsis saevissima Smith and Tetragonisca angustula Latreille). Two phthalides (3 and 4) presented insecticide potential against T. absoluta. Phthalide 4 was as toxic as piperine (positive control) and both phthalides exhibited rapid action (LT 50 < two hours). The variation in the susceptibility of T. absoluta populations to the phthalides 3 and 4 was low. Both phthalides did not present physiological selectivity in favor of the non-target species. Phthalides 3 and 4 are promising insecticides against the tomato leafminer. However, their use must follow the principles of ecological selectivity.